2018
DOI: 10.1093/ecco-jcc/jjy121
|View full text |Cite
|
Sign up to set email alerts
|

Upper Gastrointestinal Tract Involvement in Crohn’s Disease: Frequency, Risk Factors, and Disease Course

Abstract: Prevalence of upper GI tract involvement has been increasing over the past decades. Male sex and young age at diagnosis were identified as the main predictive factors for such involvement at CD diagnosis. Involvement of upper GI tract did not result in a worse outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 28 publications
4
43
0
2
Order By: Relevance
“…Present study showed that the median age of the patients with UGI involvement was significantly lower compared to those without UGI involvement. This is in accordance with a previous study by Thomas and colleagues who demonstrated a higher rate of younger patients (≤16 years) suffering from UGI tract involvement compared to those without (9.4% versus 17.8%, P = 0.005) (Greuter et al, 2018). Another study by Lopez-Siles et al observed that CD patients below 16 years of age had a striking reduction in the population of Akkermansia sp.…”
Section: Discussionsupporting
confidence: 92%
“…Present study showed that the median age of the patients with UGI involvement was significantly lower compared to those without UGI involvement. This is in accordance with a previous study by Thomas and colleagues who demonstrated a higher rate of younger patients (≤16 years) suffering from UGI tract involvement compared to those without (9.4% versus 17.8%, P = 0.005) (Greuter et al, 2018). Another study by Lopez-Siles et al observed that CD patients below 16 years of age had a striking reduction in the population of Akkermansia sp.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, some sex differences in patients with CD were revealed. Thus, an association between male sex and upper gastrointestinal tract involvement has been identified in patients with CD of the Swiss IBD Cohort Study Group[19]. Perhaps in the future, a greater focus should be placed on potential gender-related differences in IBD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our Swiss group recently described an association between sex and upper gastrointestinal tract involvement (L4 according to Montreal classification) [43]. Male sex and young age were identified as the main risk factors for the involvement of the upper gastrointestinal tract in CD patients [43]. In another study, male sex has been significantly associated with ileal disease in CD (28 vs. 20% in females) [17].…”
Section: Disease Activity and Phenotypementioning
confidence: 99%
“…IBD phenotype and location also show gender-specific differences. Our Swiss group recently described an association between sex and upper gastrointestinal tract involvement (L4 according to Montreal classification) [43]. Male sex and young age were identified as the main risk factors for the involvement of the upper gastrointestinal tract in CD patients [43].…”
Section: Disease Activity and Phenotypementioning
confidence: 99%